STUDY OF WORKING CONDITIONS ON WORKING PLACES OF ELECTRONIC COMPUTERS USERS - A. M. Lazarenkov; S. A. Horeva (Литьë и металлургия)
The results of investigations of parameters of industrial environment of the personal computers users and recommendations on decrease of influence on the organism of workers are given.